2015
DOI: 10.1016/j.redox.2015.06.014
|View full text |Cite
|
Sign up to set email alerts
|

The redox biology network in cancer pathophysiology and therapeutics

Abstract: The review pinpoints operational concepts related to the redox biology network applied to the pathophysiology and therapeutics of solid tumors. A sophisticated network of intrinsic and extrinsic cues, integrated in the tumor niche, drives tumorigenesis and tumor progression. Critical mutations and distorted redox signaling pathways orchestrate pathologic events inside cancer cells, resulting in resistance to stress and death signals, aberrant proliferation and efficient repair mechanisms. Additionally, the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(80 citation statements)
references
References 122 publications
(128 reference statements)
1
78
0
Order By: Relevance
“…Overexpression of NAF-1 resulted in enhanced respiration and glycolytic activity, supporting the possible production of excess metabolic ROS ( Fig. 2 A and B) (4,(20)(21)(22)(23). Remarkably, we were unable, however, to detect elevated levels of ROS in NAF-1(+) cells, compared with controls ( Fig.…”
Section: Enhanced Expression Of Naf-1 Is Associated With Enhanced Metsupporting
confidence: 54%
“…Overexpression of NAF-1 resulted in enhanced respiration and glycolytic activity, supporting the possible production of excess metabolic ROS ( Fig. 2 A and B) (4,(20)(21)(22)(23). Remarkably, we were unable, however, to detect elevated levels of ROS in NAF-1(+) cells, compared with controls ( Fig.…”
Section: Enhanced Expression Of Naf-1 Is Associated With Enhanced Metsupporting
confidence: 54%
“…It is well-known that large amounts of ROS, above a tumor-specific threshold, can induce inhibition of tumor cell proliferation and tumor growth [25][26][27]. Previous studies have shown that GA could promote ROS generation in various types of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…How oxidative stress is involved in these various steps is the object of revision and investigation. Furthermore, ROS may augment tumor invasion and metastasis by increasing the rates of cell migration [55,56].…”
Section: Discussionmentioning
confidence: 99%